Etnobotani Rumah Adat Suku Batak Toba di Kecamatan Sianjur Mula-Mula Kabupaten Samosir, Sumatera Utara - Ramatio Pasaribu; Tri Harsono (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to uncover and document the belief system (cosmos), local knowledge system (corpus), and the practice of plant utilization (praxis) in the traditional house of the Toba Batak Tribe. This research was carried out so that hereditary cultural knowledge about plants in the traditional house of the Toba Batak Tribe would not become extinct and would maintain its culture. This research was conducted in 2 villages in Sianjur Mula-Mula District, namely Sari Marrihit Village and Habeahan Naburahan Village. The research method is descriptive, qualitative, and quantitative. Data collection was carried out through semi-structured interview techniques, participatory observation, and documentation. The results of the study show that the Toba Batak Tribe believes that every plant used in traditional houses has a symbolic meaning, such as hope for sustenance, health, protection, harmony, unity, and sustainability of offspring. There are five species of plants from four families that are used and dominated by the Arecaceae family. The most widely used part of the plant is the trunk with the habitus of the tree. Plant processing is generally carried out by drying and the largest use is the interior elements of traditional houses. These findings show that the use of plants in the traditional house of the Toba Batak Tribe is not only functional, but also full of cultural values and local wisdom.